2021
DOI: 10.37506/ijfmt.v15i3.15503
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise and Omega 3 Supplementation to Reduce Primary Dysmenorrhea (Literature Review)

Novadri Ayubi,
Dhea Regita Sastika Putri

Abstract: Background: Primary dysmenorrhea is menstrual pain that is felt in the absence of organic disease. Hypersecretion of prostaglandins, especially PGF2a and PGE2 and increased uterine contractility are the main causes of primary dysmenorrhea during menstruation in women. Omega 3 can reduce menstrual pain by reducing levels of prostaglandins during menstruation. besides aerobic exercise can be done as one way to reduce the severity of primary dysmenorrhea.Methods: This study used a literature review method using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…In most cases, inflammation peaks 1 to 2 days after an exercise session (Chang et al, 2021;Hung et al, 2021;Muljadi et al, 2021). The current phenomenon is that around 30 million people worldwide who experience pain are usually treated with non-steroidal anti-inflammatory drugs (NSAIDs) (Ayubi & Sastika Putri, 2021;Kyriakidou et al, 2021). Giving NSAIDs after exercise is a wrong alternative for managing pain, this is because NSAIDs have a disruptive effect on the muscle growth response which has an impact on hypertrophy and muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, inflammation peaks 1 to 2 days after an exercise session (Chang et al, 2021;Hung et al, 2021;Muljadi et al, 2021). The current phenomenon is that around 30 million people worldwide who experience pain are usually treated with non-steroidal anti-inflammatory drugs (NSAIDs) (Ayubi & Sastika Putri, 2021;Kyriakidou et al, 2021). Giving NSAIDs after exercise is a wrong alternative for managing pain, this is because NSAIDs have a disruptive effect on the muscle growth response which has an impact on hypertrophy and muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…The current phenomenon is that around 30 million people worldwide who experience pain are usually treated with non-steroidal anti-inflammatory drugs (NSAIDs). (Ayubi & Sastika Putri, 2021;Kyriakidou et al, 2021). Giving NSAIDs after exercise is a wrong alternative for managing pain, this is because NSAIDs have a disruptive effect on the muscle growth response which has an impact on hypertrophy and muscle strength (Lundberg & Howatson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that muscle pain reaches its peak 24 hours after exercise [8]- [11]. In connection with this phenomenon, currently, around 30 million people worldwide who experience DOMS are usually treated with non-steroidal anti-in ammatory drugs (NSAIDs) [12], [13]. Giving NSAIDs after exercise has the effect of inhibiting hypertrophy and muscle strength.…”
Section: Introductionmentioning
confidence: 99%